2007
DOI: 10.1016/j.ijmultiphaseflow.2006.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis of local void fractions measurements for boiling hydrocarbons in complex geometry

Abstract: The present paper is part of a research program on two-phase flows and heat transfer studies in tube bundles. An experimental study was carried out to analyse the void fraction for vertical two-phase flows. Boiling across a horizontal tube bundle for three hydrocarbons (n-pentane, propane and iso-butane) under saturated conditions is investigated. The experiments were performed on a tube bundle with 45 plain copper tubes of 19.05 mm outside diameter in a staggered configuration with a pitch to diameter ratio o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…The proposed transitions are close to the bubbly-intermittent boundary of Ulbrich and Mewes [18] and significantly within the intermittent regime of Noghrehkar et al [19]. The data and flow regime boundaries of Asprin et al [20] and the flow regime boundaries of Noghrehkar et al [19] are shown in Fig. 14b.…”
Section: The Transition From Nearly Constant To Continually Decreasinsupporting
confidence: 62%
See 4 more Smart Citations
“…The proposed transitions are close to the bubbly-intermittent boundary of Ulbrich and Mewes [18] and significantly within the intermittent regime of Noghrehkar et al [19]. The data and flow regime boundaries of Asprin et al [20] and the flow regime boundaries of Noghrehkar et al [19] are shown in Fig. 14b.…”
Section: The Transition From Nearly Constant To Continually Decreasinsupporting
confidence: 62%
“…This assumption would be poor in the two-phase region above the tube bundle, or in areas where the mass flux is low, because vapour-liquid separation would be expected there. However, within the tube bundle, where frictional effects are large and the mass flux is high because of the relatively [19] with boundaries of Ulbrich and Mewes [18] and (b) flow map and data of Noghrehkar et al [19] with boundaries of Asprin et al [20]. small gap between the tubes, it is more plausible; particularly when the available experimental evidence is taken into account.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations